2022
DOI: 10.1186/s12862-022-01976-0
|View full text |Cite
|
Sign up to set email alerts
|

Complex mitogenomic rearrangements within the Pectinidae (Mollusca: Bivalvia)

Abstract: Background Scallops (Bivalvia: Pectinidae) present extraordinary variance in both mitochondrial genome size, structure and content, even when compared to the extreme diversity documented within Mollusca and Bivalvia. In pectinids, mitogenome rearrangements involve protein coding and rRNA genes along with tRNAs, and different genome organization patterns can be observed even at the level of Tribes. Existing pectinid phylogenies fail to resolve some relationships in the family, Chlamydinae being … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 124 publications
1
11
0
Order By: Relevance
“…Mollusks exhibit some of the most variable genomic architecture, molecular functions, and patterns of inheritance for mitochondria in metazoans (reviewed in Ghiselli et al 2021). Pteriomorphian bivalves are known for dynamic mitochondrial (mt) genome evolution, with Arcidae having repeatedly evolved some of the largest bilaterian mt genomes (Kong et al 2020), and Pectinidae with frequent gene order rearrangements (Malkócs et al 2022) and species with exceptionally large mt genomes (e.g., La Roche et al 1990). Currently, around 300 complete or nearly complete mitochondrial genomes are publicly available on NCBI GenBank, none of which are from Limida.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mollusks exhibit some of the most variable genomic architecture, molecular functions, and patterns of inheritance for mitochondria in metazoans (reviewed in Ghiselli et al 2021). Pteriomorphian bivalves are known for dynamic mitochondrial (mt) genome evolution, with Arcidae having repeatedly evolved some of the largest bilaterian mt genomes (Kong et al 2020), and Pectinidae with frequent gene order rearrangements (Malkócs et al 2022) and species with exceptionally large mt genomes (e.g., La Roche et al 1990). Currently, around 300 complete or nearly complete mitochondrial genomes are publicly available on NCBI GenBank, none of which are from Limida.…”
Section: Resultsmentioning
confidence: 99%
“…The only typical metazoan protein coding gene not annotated was atp8, which is commonly absent in bivalve mitogenomes (Serb and Lydeard 2003). However, recent analyses support the presence of atp8 sequences in Pectinidae (Malkócs et al 2022) and Mytilidae (Zhao et al 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Even though the current topology is highly supported, it is inconsistent with a previous phylogeny in which Aequipectinini was placed in the basal clade within Pectinidae [ 36 ]. Malkócs et al [ 24 ] concluded that different molecular markers could result in different topologies of Pectinidae, as indicated in other mollusk groups [ 25 , 37 ]. When the mitochondrial PCGs were used for phylogenetic analysis, Aequipectini always formed within Pectininae and in accordance with our result, while the topology derived from mitochondrial rRNA and nuclear H3 genes supported that of Puslednik and Serb [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Compared with other metazoans, mollusks are more prone to gene rearrangements [ 21 , 22 , 23 ]. In pectinids, mitochondrial gene rearrangements involve protein-coding genes (PCGs), ribosomal RNA (rRNA) genes, and transfer RNA (tRNA) genes, and considerable gene order changes could be detected even at the level of tribes [ 24 ]. However, the mitochondrial gene rearrangements within Pectinoidea other than Pectinidae have never been detected before.…”
Section: Introductionmentioning
confidence: 99%
“…The default parameter for coverage is set to 50% (i.e., at least 50% of the sequence of the contig has to be present in the BLAST match with the closely-related species mitochondrial genome), but this may be raised as high as 90% where the species being analysed is part of a richly-sampled group with highly constrained genome content and structure, such as Vertebrata. However, for other taxa such as Hymenoptera and Mollusca, the 50% match length cutoff is required (and indeed may be too strict) because these clades have mitochondrial genomes with highly variable gene orders [24] and a diversity of repeat lengths and copy numbers. For taxa with known variability, it is recommended that the pipeline is run using multiple different references (using the findMitoReference.py -n flag) and exploring different match length proportions.…”
Section: Discussionmentioning
confidence: 99%